HOW DOES CORPORATE GOVERNANCE LEVERAGE ORGANIZATIONAL PERFORMANCE: A SURVEY WITH SUGGESTIONS AND NOTES FOR FURTHER RESEARCH - Almashhadani M. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
In this research, internal control mechanisms (ICM) and organizational performance are surveyed and also focus on the corporate governance system (CGS) reality and other internal control mechanisms’ roots in the history. The paper offers the background of the origin of CGS and its mechanisms. Such a system emerged for a long time ago where mistakenly some scholars, researchers and other academic staff in the universities and institutions that it appeared at the beginning of the twentieth century. Therefore, this research aims at introducing some valuable information that will probably be as a guide for several parties such as academics, scholars and both current and potential investors. In addition, the current research suggest a solution for the clear gap in the previous studies that have dealt with the relation between ICM and organizational performance based on a survey in the studies that have been done in the previously in the literature review. Furthermore, there will be an explanation of the main theories in this regard.